PERAN KEARIFAN LOKAL MASYARAKAT SEKITAR GUNUNG TIMAU DALAM MENDUKUNG KETAHANAN SOSIAL EKONOMI RUMAH TANGGA AMFOANG TENGAH - Hen’st Valen Adip Benu; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Local wisdom refers to social norms, values, and practices that develop and flourish in the daily lives of the adat community and support strategic efforts to improve the socio-economic 1conditions of households. This study is based on the fact that the community in the vicinity of Gunung Timau, Amfoang Tengah District, Kupang Regency, still adheres to local customs despite the increasing pace of modernization and construction. The purpose of this study is to examine various forms of local wisdom and analyze their contribution to improving the socioeconomic conditions of households in Amfoang Tengah. The methodology used in this study is descriptive qualitative with data collection techniques such as literary studies and structured research. The data analysis process is based on the interactive Miles and Huberman model, which includes data reduction, data analysis, and systematic conclusions. The study's findings indicate that local wisdom practices, such as customary forest management, water power conservation, and a culture of mutual assistance, are crucial in strengthening social solidarity and increasing the economic strength of local households. Because of this, local wisdom must receive attention and be integrated into formal education and construction policies in order to support future rural development.